1978
DOI: 10.3181/00379727-157-39979
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Metabolism of Glycerol by Hyperlipemic and Normolipemic Rats

Abstract: Supported by the BLY Memorial Research Fund and the Veterans Administration Hospital. Present address: Department of Foods and Nutrition, University of Georgia, Athens, Georgia 30602 (Dawson Hall). Wistar rats were purchased from Charles River Breeding Laboratories, Wilmington, Massachusetts. The original BHE animals were purchased from Flow Laboratories, Dublin, Virginia. The BHE colony has been moved from this facility to the NIH Animal Resource Center.5 0037-9727/78/1571-0005$01 .OO/O Copyright 0 1978 by t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Other measurements. Consistent with previous reports (3,4,10), strain and diet differences were observed in the triglyceride and free glycerol levels in the fasting and nonfasting blood ( Figs. 7 and 8).…”
Section: Resultssupporting
confidence: 93%
“…Other measurements. Consistent with previous reports (3,4,10), strain and diet differences were observed in the triglyceride and free glycerol levels in the fasting and nonfasting blood ( Figs. 7 and 8).…”
Section: Resultssupporting
confidence: 93%
“…This observation was expected; however, they also reported an increase in fatty acid oxidation. The latter observation is consistent with our finding of a tenfold elevation in serum free glycerol, a product of peripheral tissue lipolysis, and an increase in hepatic glycerol use for glucose synthesis and fatty acid reesterification (Berdanier et al, 1978(Berdanier et al, , 1982. Detailed studies of frozen-clamped hepatic tissue from stock-dietfed rats, (a process in which large clamps, immersed in liquid nitrogen, smash the excised liver to the thinness of a potato chip) revealed that liver cells had elevated phosphorylation and redox states, findings consistent with elevated rates of hepatic lipogenesis (Berdanier et al, 1979).…”
Section: Early Phenotype Detectionsupporting
confidence: 92%
“…By the fifth generation of inbreeding and selection, rats were found to have an elevated lactate:pyruvate level in blood and hepatic tissue (11,12). By the seventh generation, rats were found to have elevated blood glycerol levels (9) and elevated rates of lipolysis as well as hepatic triacylglyceride and cholesterol synthetic rates (52). By the seventh generation, rats were found to have elevated blood glycerol levels (9) and elevated rates of lipolysis as well as hepatic triacylglyceride and cholesterol synthetic rates (52).…”
Section: The Bhe/cdb Ratmentioning
confidence: 99%
“…Genetically obese rats, such as the Zucker diabetes rat and the ob/ob mouse, have a fatty liver but are obese regardless of diet and these animals develop a form of diabetes that is related to their body fat stores. Interestingly, the elevated lipogenic characteristic is not associated with an increase in body fat stores primarily because this elevation is also accompanied by an increase in lipolysis (9,52). The BHE/Cdb rat can have a brief period of hyperinsulinemia early in life (6) but this does not always occur.…”
Section: The Bhe/cdb Ratmentioning
confidence: 99%